ENTERPRISE ARCHITECTURE FOR HEAVY EQUIPMENT DEALER IN INDONESIA USING BUSINESS MODEL CANVAS - Haludin, Guntur; Indrajit, Richardus Eko; Dazki, Erick (Jurnal Teknik Informatika (Jutif), 2022)
Indonesia as one of the countries endowed with abundant natural resources drives the development of the mining, plantation and construction industries that contribute to economic growth and state revenue. In practice, both the mining and plantation and construction industries require heavy equipment to conduct their business operations where heavy equipment dealers supply this need. Heavy equipment dealers in addition to selling heavy equipment units, also provide after-sales services such as supplying spare parts and maintenance services ranging from routine maintenance to total maintenance services. In line with the development of technology, heavy equipment dealers need to conduct digital transformation to maximize business opportunities and optimize their business operations. For this, it is necessary to plan a business model by creating a comprehensive enterprise architecture, starting from the business aspects, application, the information, the technology, and core business processes. The paper will explain the process to develop the enterprise architecture using business model and further detailed with the three main revenues using the ArchiMate diagram to show the interaction between the business processes with the applications, databases, technology, and business actors who play a role in the process.